2009
DOI: 10.1111/j.1399-5618.2009.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functions in patients with bipolar I and bipolar II disorder

Abstract: BP-I was characterized by reduced performance in verbal memory, working memory, psychomotor speed, and executive function, while BP-II patients showed a reduction only in working memory and psychomotor speed. Cognitive impairment existed in both subtypes of bipolar disorder, and was greater in BP-I patients. Rehabilitation interventions should take into account potential cognitive differences between these bipolar subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 47 publications
10
77
0
2
Order By: Relevance
“…Similarly, some authors suggest that BD I patients have more widespread cognitive dysfunction than BD II patients (Simonsen et al 2008 ;Hsiao et al 2009). In the study by Simonsen et al (2008) BD II patients showed reduced performance on certain measures of attention and executive function (working memory, verbal fluency and interference control), while the BD I group showed reduced performance on all verbal memory measures and on most measures of attention and executive function (working memory, fluency, interference control and set-shifting).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, some authors suggest that BD I patients have more widespread cognitive dysfunction than BD II patients (Simonsen et al 2008 ;Hsiao et al 2009). In the study by Simonsen et al (2008) BD II patients showed reduced performance on certain measures of attention and executive function (working memory, verbal fluency and interference control), while the BD I group showed reduced performance on all verbal memory measures and on most measures of attention and executive function (working memory, fluency, interference control and set-shifting).…”
Section: Discussionmentioning
confidence: 98%
“…In another more recent study BD II patients in an interepisodic phase had an intermediate performance between BD I and healthy subjects (Hsiao et al 2009). In a study (Harkavy-Friedman et al 2006) assessing BD patients with a depressive episode, BD II patients had a worse performance in the Digit Symbol subtest, and performed worse than BD I patients in the Stroop Test.…”
Section: Attention and Psychomotor Speedmentioning
confidence: 90%
See 1 more Smart Citation
“…BD II has been shown to be a categorically different entity than BD I in genetic, [15][16][17] biological, 18 neuropsychological, 19 and clinical [20][21][22] aspects. Thus, BD II is not likely integrated with BD I at the level of personality traits as well.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10][11][12][13][14] Regrettably, none of these studies presented separate data on BD I and BD II patients; rather, subjects included mixed BDI and BD II patients or only those with BD I. As BD II differs from BD I in genetic, [15][16][17] biological, 18 neuropsychological, 19 and clinical [20][21][22] aspects, the personality traits of individuals with BD II and BD I should be assessed separately.…”
Section: Introductionmentioning
confidence: 99%